Can a time-varying equilibrium real interest rate explain the excess sensitivity puzzle? - Annika Alexius; Peter Welz (Uppsala University, Department of Economics, 2006)
The strong response of long-term interest rates to macroeconomic shocks has typically been explained in terms of informational asymmetries between the central bank and private agents. The standard models assume that the equilibrium real interest rate is constant over time and independent of structural shocks. We incorporate time-variation in the equilibrium real interest rate as function of structural shocks to e.g. productivity and demand. This extended model implies that forward interest rates at long horizons move about 40 basis points as the short-term interest rate increases one percentage point. In terms of regressions of changes in long-term interest rates on changes in the short-term interest rate, including a time-varying equilibrium real interest rate explains about half of the puzzle.
urn:nbn:se:uu:diva-83094
Keywords: C51; E43; E52; 330; Term structure; equilibrium real interest rate; unobserved components model; Wirtschaftslage; Schock; Realzins; Zinsparität; Zinsstruktur